The pioneer woman cooks : food from my frontier - Drummond, Ree (William Morrow, 2012)
A mouthwatering collection of the simple-but-scrumptious recipes that rotate through Ree's kitchen on a regular basis, from perfect pancakes to honey-plum-soy chicken, from cowgirl quiche to blackberry chip ice cream.